2004
DOI: 10.1677/joe.1.05832
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of amino acids and glucose on insulin secretion from isolated rat or mouse islets

Abstract: Glucose and the combination of leucine and glutamine were used to stimulate insulin secretion from rat islets during a dynamic perifusion and the responses obtained were compared with those elicited from mouse islets under identical conditions. In rat islets, glucose (15 mM) or the amino acid combination of 10 mM glutamine plus 20 mM leucine were most efficacious and peak secondphase insulin release responses were 20-to 30-fold above prestimulatory rates. In contrast to rat islet responses, sustained second-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
(84 reference statements)
1
8
0
2
Order By: Relevance
“…We show that in the donor tested, treatment with GW8510 and a general kinase inhibitor, staurosporine, potentiated both basal and the glucose-stimulated insulin secretion. In addition, a previous report indicates that wortmannin, a phosphatidylinositol 3-kinase inhibitor, augmented insulin secretion at 15 mM glucose [43]. Currently available methodology does not enable us to distinguish between the effects on insulin release from beta cells, which represent the majority of the islet endocrine cell population, and potential contributions from other islet cell types.…”
Section: Discussionmentioning
confidence: 98%
“…We show that in the donor tested, treatment with GW8510 and a general kinase inhibitor, staurosporine, potentiated both basal and the glucose-stimulated insulin secretion. In addition, a previous report indicates that wortmannin, a phosphatidylinositol 3-kinase inhibitor, augmented insulin secretion at 15 mM glucose [43]. Currently available methodology does not enable us to distinguish between the effects on insulin release from beta cells, which represent the majority of the islet endocrine cell population, and potential contributions from other islet cell types.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent comparative studies between mouse and rat islets have established that stimulation of this pathway is less robust in mouse islets in vitro (4,23,26,42,56). This finding has led to several reports investigating the mechanisms underlying the different degrees of stimulation of second-phase secretion in mouse and rat islets, including glyceraldehyde (23), cAMP (26), protein kinase A (48), phospholipase C (53,56), and amino acids (25,55) and has even led to speculation that the mouse may not be a good model for examining insulin secretion as it relates to humans, which have a robust second phase (26).…”
Section: Discussionmentioning
confidence: 99%
“…In general, activation of the insulin-signal cascade through activation of insulin receptor tyrosine kinase was thought to down-regulate GSIS. Studies using PI3 kinase inhibitors demonstrated that pharmacological blockage of the insulin-signaling pathway could potentiate GSIS (Eto et al, 2002;Zawalich et al, 2004). Diminished insulin signaling by reduced expression of the insulin receptor also showed enhanced GSIS (Ohsugi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%